The Process of Message Production Among Whatsapp Social Media Users - Pratikto, Riyodina G.; Kholil, Kholil; Widaningsih, Titi; Jamalullail, Jamalullail (Eastasouth Institute, 2025)
As a result of developments in technology and information, the way individuals communicate has changed. This is also the case with the SMAN 3 Bandung Class of '82 Alumni Association, which uses a WhatsApp group (WAG) as a platform to gather and exchange information. However, there is a problem, namely that the dynamics of communication within the ikasma3badg82 WAG cannot always be conveyed in their entirety. The researcher argues that dishonesty in conveying messages within the WAG is part of an effort to maintain solidarity among group members. The objectives of this study include (1) to determine the message production process within the ikasma3bdg82 WAG and (2) to determine how the message production process within the ikasma3bdg'82 WAG is related to the characteristics of its members. The research methodology uses a constructivist paradigm and a qualitative approach. The results of the study include (1) The message production process carried out by members of the ikasma3bdg82 WAG, between passive and active members, is fairly balanced. (2) Based on Trait Theory, members of the ikasma3bdg82 WAG can be classified into Conversational Narcissism, Argumentativeness, and Social Communication Anxiety. The uniqueness of this study is the emergence of the Super Conversational Narcissism component, which is a development of Littlejohn's Trait Theory.